Training and Development of Cassava Chips MSMEs in Lingga Tiga Village: Efforts to Increase Capacity and Competitiveness of Local Products - Abd. Rasyid Syamsuri; Siti Lam'ah Nasution; Rika Syahmewah; Pera Herawati; Hidayatul Majidah (International Journal of Community Service Implementation, 2024)
Lingga Tiga Village has great potential in developing cassava chips MSMEs, but still faces various obstacles such as limitations in management, marketing and product innovation. This community service aims to provide training and assistance to cassava chips MSMEs in Lingga Tiga Village to increase production capacity, business management and marketing strategies. The methods used include training, mentoring and evaluation. The results of the service show an increase in the knowledge and skills of MSME players in managing businesses, as well as the formation of more effective marketing strategies. It is hoped that this activity can encourage village economic growth and increase the competitiveness of cassava chips products in the wider market.